2008
DOI: 10.4269/ajtmh.2008.78.872
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Vectors in Areas of Plasmodium falciparum Epidemic Transmission in the Amazon Region, Brazil

Abstract: The main vectors of malaria in Brazil are Anopheles darlingi, An. aquasalis, and some species of the An. albitarsis complex, whereas others have questionable importance with regard to the disease transmission. To identify these vectors in the State of Pará, Brazil, in a high-prevalence P. falciparum area, 565 anophelines were captured and identified while the seasonal variation and daily biting activity were determined. Of the seven anopheline species (An. strodei, An. albitarsis s.l., An. rondoni, An. darling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…Human reservoirs can maintain transmission in areas of low, moderate, or high endemicity because they can infect mosquitoes [42]. Despite the role of subclinical infection in maintaining malaria transmission, little is known about the factors that determine its occurrence and whether it is associated with human protective immune responses [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human reservoirs can maintain transmission in areas of low, moderate, or high endemicity because they can infect mosquitoes [42]. Despite the role of subclinical infection in maintaining malaria transmission, little is known about the factors that determine its occurrence and whether it is associated with human protective immune responses [41].…”
Section: Discussionmentioning
confidence: 99%
“…subclinical infections in blood donors living either in forested areas or urban regions intermixed with forest fragments suggests that some evolutionary mechanisms are modulating the virulence of P. falciparum and P. vivax in a way that does not negatively affect survival of the parasite, humans, mosquitoes, and non-human primates that seem to be involved in malaria transmission in the Atlantic Forest. The dynamics of human malaria transmission in the Brazilian Amazon forest seems to involve similar evolutionary mechanisms that lead to subclinical infections in humans [42], and transmission cycles that involve humans and other mosquito species as vectors (in addition to An. darlingi ) [51], and non-human primates, which were recently found to be infected with P. falciparum [52].…”
Section: Discussionmentioning
confidence: 99%
“…Mosquitoes of the genus Anopheles were present in the samples in relatively small numbers representing 353 individuals of all species or 1.8% of the total number of individuals caught. They were almost exclusively nocturnal, as is reported in studies worldwide [19,20]. From the subgenus Anopheles maculipennis, the species An.…”
Section: Discussionmentioning
confidence: 60%
“…At Sedlec, Culex modestus Ficalbi was a clearly dominant species from May to the end of June (Table 2, 4), with the highest capture (6,952 females) recorded in the second sampling trip (20)(21)(22). However, between 31 August and 2 September when the incidence of Aedes vexans (Meigen) and, to a lesser extent, Ochlerotatus sticticus (Meigen) peaked, only 225 Cx.…”
Section: Resultsmentioning
confidence: 99%
“…darlingi can present a marked early biting behavior and high outdoor-to-indoor biting ratio [81] in some areas, although a late biting behavior and indoor preference have also been described [82]. Very little is currently known about the biting behavior of other malaria vectors in Amazonia [81,83]. The marked regional variation in vector behavior, which cannot be anticipated without careful baseline entomological studies, has been suggested to cause large differences in the estimates of ITBN efficacy obtained in three randomized community trials in Peru and Nicaragua [84].…”
Section: A Role For Insecticide-treated Bed Nets In Brazil?mentioning
confidence: 99%